Optimal Design of a Hybrid Energy System for the Supply of Clean and Stable Energy to Offshore Installations - Riboldi, Luca; Alves, Erick F.; Pilarczyk, Marcin; Tedeschi, Elisabetta; Nord, Lars O. (Frontiers in Energy Research, 2020)
This paper presents an innovative hybrid energy system for stable power and heat supply in offshore oil and gas installations. The proposed concept integrates offshore wind power, onsite gas turbines and an energy storage system based on fuel cell and electrolyzer stacks. It is expected to be an effective option to decarbonize the offshore petroleum sector as it allows a more extensive exploitation of the offshore wind resource by means of energy storage. To ascertain its potential, an integrated model was developed. The integrated model allows to simulate the process and electric grid performances. The inclusion of both domains provides a comprehensive picture of a given design operational performance. The feasibility of the proposed concept was first investigated through a parametric analysis where an understanding of its potential and limitations was gained. A rigorous optimization was then implemented to identify the designs resulting in the best performances and ultimately to obtain a comprehensive picture of the suitability of the concept. It is shown that a well-designed system can reduce carbon emissions compared, not only to a standard concept based on gas turbines (almost 1300 kt less CO2 emissions, making up for a relative 36% reduction), but also to the integration of a wind farm alone (more than 70 kt less CO2 emissions, making up for a relative 3% reduction, but complying with grid dynamics requirements). Moreover, the energy storage system brings benefits to the electric grid stability and allows the integration of large wind power capacity without overpassing the 2% maximum frequency variation (as it is the case without energy storage). Not least, the optimization showed that the definition of an optimal design is a complex task, with little margin to further gains in terms of carbon emissions, likely due to technological limitations.